One-Step Approach to Identifying Gestational Diabetes Mellitus: Association With Perinatal Outcomes. Issue 4 (October 2018) - Pocobelli, Gaia; Yu, Onchee; Fuller, Sharon; Fraser, James R.; Wartko, Paige D; Chen, Lu; Newton, Katherine M.; Dimer, Jane; McCulloch, David K.; Warwick, Susan; Dublin, Sascha
Abstract : OBJECTIVE: To compare perinatal outcomes before and after a clinical guideline change from a two-step to a one-step approach to screening for gestational diabetes mellitus (GDM). METHODS: We conducted a before–after cohort study of women with singleton live birth deliveries within Kaiser Permanente Washington, a mixed-model health plan in Washington state. We used Kaiser Permanente Washington electronic health data and linked birth certificates. We compared outcomes before (January 2009–March 2011) and after (April 2012–December 2014) the guideline change among women who received prenatal care from health care providers internal to Kaiser Permanente Washington (n=4, 977 before, n=6, 337 after). We made the same comparison among women who received prenatal care from external health care providers (not exposed to the guideline change; n=3, 386 before, n=4, 454 after) to control for time trends unrelated to the guideline change. Adjusted relative risks and 95% CIs were estimated using Poisson generalized estimating equations. RESULTS: After the guideline change, receipt of the one-step approach became widespread among women cared for by Kaiser Permanente Washington internal providers (87%), and use of insulin increased 3.7-fold from 1.2% to 4.4%. Among women cared for by Kaiser Permanente Washington internal providers, GDM increased from 6.9% to 11.4%, induction of labor from 25.2% to 28.6%, neonatal hypoglycemia from 1.3% to 2.0%, and outpatient nonstress testing from 134.6 to 157.0 test days per 100 women. After accounting for background trends in outcomes (based on the women cared for by external providers), the guideline change was associated with increased incidence of GDM (relative risk [RR] 1.41, 95% CI 1.17–1.69), labor induction (RR 1.20, 95% CI 1.09–1.32), neonatal hypoglycemia (RR 1.77, 95% CI 1.14–2.75), and nonstress testing (RR 1.12, 95% CI 1.02–1.24% per 100 women). There was no association with other outcomes including cesarean delivery or macrosomia. CONCLUSION: Adopting the one-step approach was associated with a 41% increase in the diagnosis of GDM without improved maternal or neonatal outcomes. Abstract : Our findings do not suggest a benefit of the one-step over the two-step approach to gestational diabetes testing.